The Analysis of Changes in the Level of Poverty and the Main Characteristics of the Poor in the South of Russia - Oleynik, Olga; Pridachuk, Maksim (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serii͡a︡ 3, Ėkonomika, pravo, 2016)
The poverty is a multifaceted and diverse phenomenon, it varies in time and space. In the economic literature, various approaches are used to measuring poverty. The article deals with the methods of measuring poverty in the Russian Federation. When analyzing the changes in the level of poverty and the main characteristics of the poor in Southern Russia, the authors relied on official statistical information published in editions of the Federal State statistics service. Poverty trends are revealed for the period of four years (2011-2014) in the dynamics and by the constituent entities of the Russian Federation, within the Southern and North Caucasus Federal Districts. The authors identified poverty ratio changes in various Southern subjects of the Russian Federation. The level of well-being of the population and the poverty ratio fluctuations in the Southern regions of the Russian Federation are estimated. It is shown that the Southern regions are characterized by a low level of material well-being. The analysis revealed a trend of increasing the proportion of poor households in rural areas. Rural populations are the most vulnerable to the risk of poverty, mainly because of the high concentration of poor households and minimal income levels which increases the vulnerability of households. The analysis of the distribution of poor households according to their composition, revealed a high proportion of households consisting of three or more people. It is determined that the hallmark of Russian poverty is high “child poverty”. It is substantiated that the socio-economic indicators of poverty let identify the general trends in poverty levels of the subjects of Southern and North Caucasus Federal districts. The outcome of the present study consists in the withdrawal of the main priorities for combating poverty in the South of Russia.